(untitled) (Journal of Oriental Studies, 2016)
В этой статье рассматривается изменения политической жизни Египта, борьбы политической партий 80-90-х гг. ХХІ века. This article is dedicated to the changes in political life of Egypt, the struggle of political parties in 1980-1990-s of twenty-first century.